Design complexity: assessing cross-modal correspondence between complex food images and the desire to eat - Nwankwo-Ojionu, Chimeziem Elijah; Adzharuddin, Nor Azura; Waheed, Moniza; Mohd Khir, Azlina; Elijah, Emem Chimeziem (Instituto Superior de Entre Douro e Vouga, 2024)
Customers' visualization influences their choice of foods based on the appearance and presentation of food images in marketing communication. Despite the momentous role of complex food images in gaining consumers' attention, the propositions of complex food image effects are rare in sensory cues and food advertising literature. The present study investigated whether complex food images increase consumers' evaluation and predisposition to desire to eat in two experiments with a post-test only between-subject design. Participants (N=300) in four design complexity principles 150 (75 complex and 75 simple), 150 (75 aesthetic and 75 displeasing). The findings from the two studies revealed that complex and aesthetic food images significantly increased the desire to eat when the food images in the advertisement are elaborate, attractive, bright, arousal, multiple, and satisfying—indicating a cross-modal correspondence between complex food images and the desire to eat. Palatable positively mediated the relationship between complex, aesthetic food images and the desire to eat. Theoretical and practical implications for design complexity in food marketing communication are discussed.